Generation and nature of water-tolerant Lewis acid sites in InxSn10−xOy/Al2O3 catalysts as active centers for the green synthesis of methyl lactate from glucose. Issue 5 (3rd February 2023) - Zhao, Zhenxiang; Yang, Jun; Xu, Ningkun; Nan, Tian; Wu, Pingping; Wang, Chunzheng; Wang, Xiaohua; Bai, Peng; Yan, Zifeng; Mintova, Svetlana
Abstract : The improvement of methyl lactate yield was achieved by constructing water-tolerant Lewis acid sites, which were generated by reducing hydroxyl groups and increasing coordinatively unsaturated sites. Abstract : Solid Lewis acid catalysts are commonly used in the synthesis of methyl lactate (MLA). However, water as a solvent, reactant, or by-product adsorbed on the Lewis acid sites (LAS) resulted in the deactivation of the LAS. In this study, highly dispersed In–Sn oxide on the surface of an alumina support was prepared using interconnected In2 O3 and SnO2 . The highly dispersed In–Sn oxides effectively decreased the OH groups of the catalyst, leading to the decrease of the residual organics and inhibiting the deleterious effect of water on LAS. Besides, the Sn doping resulted in abundant coordinatively unsaturated sites (CUS) on the catalyst surface. The CUS were further partially hydrolyzed, forming new OH groups under the action of water during the MLA synthesis, thus leading to an increase in the LAS activity. Therefore, after the Sn doping, more LAS were detected in the presence of water, confirming that the In x Sn10− x O y /Al2 O3 catalyst had more water-tolerant LAS. Under the synergy of lower hydroxyl density and more water-tolerant LAS, an MLA yield of 57.6% was achieved on the In7 Sn3 O y /Al2 O3 catalyst, which is the highest reported for the non-zeolite metal oxide catalysts up to now. This work provided a new strategy for the design of non-zeolite metal oxide catalysts with decreased OH groups, increased CUS and no LAS deactivation in the presence of water.